International trends in company tax collective investment vehicles - Andy Hutt; Alicia Tan; Grant Wardell-Johnson (The Australian Government, The Treasury, 2017)
The world has become an increasingly integrated and global place, creating opportunities for businesses to expand their networks beyond physical borders. This presents both opportunities and challenges to the corporate tax system, as the rise of intangibles and the digital economy creates difficulties in assessing and taxing profits and capital. This study aims to provide a cross-country comparison, drawing out the similarities and differences between corporate tax systems. Australia's corporate tax system was chosen as the centre of this study. The major North American (United States and Canada), European (United Kingdom, Germany, France, Netherlands and Ireland) and Asian (China, India, New Zealand, Japan, Korea, Hong Kong, Singapore and Indonesia) economies were selected, as they were identified as major players in the global economy and important trading partners to Australia. This is not an in-depth cross-country analysis, rather this study aims to provide a snapshot of key trends of corporate tax systems around the world. Four common indicators have been chosen for this study. The ratio of company tax to GDP has been chosen as an indicator to assess a country's reliance on the company tax base. The statutory company tax rate and thin capitalisation rules have been chosen as levers available to governments in shaping the corporate tax system. Collective investment vehicles were also chosen as an interesting and alternate lever available to governments in attracting foreign investment.
Keywords: 330